Integrasi Literasi Kritis dalam Pengajaran Bahasa: Strategi Inovatif untuk Mengembangkan Pemikiran Reflektif dan Kompetensi Interkultural: Integrating Critical Literacy in Language Teaching: An Innovative Strategy to Develop Reflective Thinking and Intercultural Competence - Firdaus, Saiyidinal (Journal of Literature and Education, 2025)
This study explores the integration of critical literacy in language teaching as an innovative strategy to foster students’ reflective thinking and intercultural competence. Drawing on Freire and Giroux’s critical literacy framework, Dewey and Schön’s reflective thinking, and Byram and Deardorff’s intercultural competence models, the research combines literature review, best practice analysis, and theoretical case studies. Findings reveal that critical literacy equips students to evaluate texts and discourses embedded with ideological values, while reflective thinking enhances self-awareness and social engagement. Intercultural competence, in turn, strengthens adaptability in cross-cultural communication. Major challenges identified include limited understanding of socio-cultural issues, difficulties in analyzing multimodal texts, implicit bias, and deeply ingrained cultural stereotypes. To address these issues, the study proposes strategies such as authentic text discussions, multimodal discourse analysis, intercultural simulations, and reflective practices. Practical solutions, including contextual scaffolding, step-by-step multimodal training, and interactive cross-cultural simulations, are recommended to ensure effective implementation. The research emphasizes the need for a holistic pedagogical approach that integrates critical literacy, reflection, and intercultural competence to develop learners who are critical, adaptive, and inclusive. Ultimately, such integration prepares students not only to succeed academically but also to engage meaningfully within increasingly complex global societies.